2014
DOI: 10.1186/1475-2891-13-71
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation with ferrous sulfate or iron bis-glycinate chelate on ferritin concentration in Mexican schoolchildren: a randomized controlled trial

Abstract: BackgroundIron deficiency is one of the most common nutritional deficiencies worldwide. It is more prevalent when iron requirements are increased during pregnancy and during growth spurts of infancy and adolescence. The last stage in the process of iron depletion is characterized by a decrease in hemoglobin concentration, resulting in iron deficiency anemia. Iron deficiency, even before it is clinically identified as anemia, compromises the immune response, physical capacity for work, and intellectual function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 30 publications
1
29
1
4
Order By: Relevance
“…It was interesting to note that in the present study despite 3 months of iron therapy, significant proportion (29.7%) of children continued to have low ferritin levels. A study from Mexico showed that after 3 months of daily iron supplementation, 10% of children still remain iron‐deficient (ferritin < 12 µg/L) . A systematic review of studies concluded that daily iron supplementation in pre‐school children reduces the risk ratio of iron deficiency to 0.21 (95% confidence interval 0.07–0.63).…”
Section: Discussionmentioning
confidence: 99%
“…It was interesting to note that in the present study despite 3 months of iron therapy, significant proportion (29.7%) of children continued to have low ferritin levels. A study from Mexico showed that after 3 months of daily iron supplementation, 10% of children still remain iron‐deficient (ferritin < 12 µg/L) . A systematic review of studies concluded that daily iron supplementation in pre‐school children reduces the risk ratio of iron deficiency to 0.21 (95% confidence interval 0.07–0.63).…”
Section: Discussionmentioning
confidence: 99%
“…It has reported that IDA affects the mental and physical health of children, the developmental stage for teenagers, or the chronic fatigue and compromised immune system for adults [6]. The bioavailability and iron absorption from the daily diet are influenced by the type and quantity of iron present in food as well as by the presence of inhibitors and promoters of iron absorption in the diet and the individual's iron status [7]. So iron supplements have been widely used to overcome IDA.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation programmes are expensive because personnel are required for counselling, distributing supplements and monitoring to improve compliance. It has been well documented that not all anaemic persons become non-anaemic after three-months of daily supplementation; once supplementation is stopped some of those who became non-anaemic may become anaemic (27)(28)(29)(30). Taking these into consideration, the WHO advocates food fortification with iron for sustained improvement in iron intake in countries with low iron intake (31).…”
Section: Discussionmentioning
confidence: 99%